FAKTOR SOSIAL EKONOMI DAN LINGKUNGAN PADA AGROWISATA MUNCAK TEROPONG LAUT DI DESA MUNCAK KABUPATEN PESAWARAN PROVINSI LAMPUNG - Dian Mukri; Raden Hanung Ismono; Muhammad Ibnu (Lampung University, 2021)
This research aims to determine factors that affect the frequency of tourists visits, economic impacts generated, and the positive and negative externality impacts to community surrounding of Muncak Teropong Laut Agrotourism area. Data collection was conducted from November 2018 to February 2019. Respondents were 80 visitors and 7 people from surrounding community. Factors affecting the frequency of visits were analyzed using multiple linear regression whereas economic impact analysis and externalities are explained by qualitative descriptive. The study shows that factors affecting the number of visits to Muncak Teropong Laut are age, education, income, travel expenses, time of visit, and facilities. Economic impact of the community surrounding Muncak Teropong Laut is increased in business activity such as small vendors that gain IDR750,000.00 to IDR1,000,000.00 per month. Other positive externality is absorption of labour. Negative externalities include cost of road repairs and medical expenses.Key words: agrotourism, community economics, externalities